From Recall to Commitment: The Influence of Distributive Justice and Severity Recall on Affective Trust and Corporate Reputation in the Automotive Sector - Astira, Ameylia Ayu; Yulianto, Edy; Rahimah, Anni (Universitas Airlangga, 2025)
Objective: Widespread product recalls present a significant challenge in the global automotive industry, often leading to reputational damage and a decline in customer loyalty. Understanding how customers respond after a recall is essential, particularly in determining whether their commitment diminishes or remains intact. This study examines the influence of distributive justice, recall severity, affective trust, and corporate reputation on the affective commitment of customers who have experienced an automotive product recall for repair. The theoretical framework for this study is based on Rawls’ theory, social exchange theory, resource advantage theory, and attribution theory. Design/Methods/Approach: Data for this study were collected through an online questionnaire, with a total of 220 eligible respondents participating. The study utilizes partial least s equation modeling (PLS-SEM) to analyze the impact of distributive justice and recall severity on consumers' affective trust, company reputation, and affective commitment. Findings: This study found that distributive justice and recall transparency enhance affective trust and corporate reputation, ultimately strengthening customer commitment. A fair and transparent recall strategy can transform a crisis into an opportunity to foster loyalty. Originality/Value: The originality of this research lies in its exploration of previously unexamined interrelationships among variables in the context of automotive product recalls. Additionally, the inclusion of these specific variables offers a more accurate and comprehensive understanding from the consumer's perspective. Practical/Policy implication: Our research provides automotive companies with a strategic framework to turn product recalls into opportunities by leveraging personalized communication, enhancing service quality, implementing systematic problem-solving, and fostering trust-building initiatives. These strategies help sustain customer relationships during recalls by emphasizing emotional engagement, rigorous vehicle inspections, transparent communication, and community-driven programs.